Community Treatment for Opioid Use Disorders in Urban and Rural Veterans. Issue 2 (6th December 2019) - Turvey, Carolyn L.; Lund, Brian C.; Jones, DeShauna; Arndt, Stephan
Abstract: Purpose: The recent opioid crisis is characterized by a relatively greater increase in opioid use disorder and related mortality in rural populations when compared with urban populations. 1‐5 As almost a quarter of our nation's veterans reside in rural settings, the United States Veterans Health Administration (VHA) is interested in the impact of this epidemic on rural veterans. This study aims to develop a comprehensive understanding of the trends in substance use disorders (SUD) in veterans seeking treatment from community, non‐VHA providers. Methods: Using Substance Abuse and Mental Health Services Administration (SAMHSA)'s Treatment Episode Data Set (TEDS), this study presents the prevalence of treatment for veterans seeking initial admission into publicly funded non‐VHA SUD treatment centers for years 2011‐2016. Comparisons were made for all SUD types. Multivariate trend analysis based on annual data from 2011 to 2016 compared urban and rural veterans for opioid use disorder treatment. Findings: Both urban and rural veterans had comparable rates of treatment for SUD, though rural veterans had slightly higher rates of injectable (11.2% vs 8.7%; P < .001) and opiate drug use disorder admissions (20.7% vs 18.1%; P = .014). Both urban and rural showed an increase in admissions for opioid, heroin, and injectable drug use disorders between 2011 and 2016 ( P < .001). Conclusions: Comprehensive understanding of veteran SUD and treatment should include national‐level data on community non‐VHA treatment. SAMHSA's TEDS for years 2011‐2016 provides clinical information for more than 90, 000 veterans and indicates continued increase in treatment seeking for opioid use disorders, particularly for rural veterans.